2023
DOI: 10.1039/d3ma00300k
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of hydrophobic mixed organogels with complementary hydrogen-bond donor–acceptor sites: removal of heavy metal ions Hg2+, Cd2+ and Pb2+ from aqueous solution

Abstract: The hydrophobic organogel G8GE with metallogel formation and shape forming ability is used in the removal of Hg(ii), Cd(ii) and Pb(ii) from contaminated water with low cost-effected reusability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…However, with the synthesized gelation component CBTC , a suitable solvent composition could not be found to get it self-assembled into a stable gel. However, it has been observed and reported that adding other molecules of similar symmetry and providing complementary hydrogen bond donor–acceptor sites , could induce gelation in the whole system . Among the available library of molecules, trimesic acid with a similar symmetrical structure with the probability of π–π stacking among aromatic rings and provision of complementary hydrogen bond donor–acceptor sites is selected for further investigation to use as the second gelation component.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, with the synthesized gelation component CBTC , a suitable solvent composition could not be found to get it self-assembled into a stable gel. However, it has been observed and reported that adding other molecules of similar symmetry and providing complementary hydrogen bond donor–acceptor sites , could induce gelation in the whole system . Among the available library of molecules, trimesic acid with a similar symmetrical structure with the probability of π–π stacking among aromatic rings and provision of complementary hydrogen bond donor–acceptor sites is selected for further investigation to use as the second gelation component.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous reports, , the concept of complementary hydrogen bond donor–acceptor sites was introduced, which accounts for the strengthening and improved properties of the gels. The presence of complementary hydrogen bond donor–acceptor sites in trimesic acid makes it an ideal candidate for use as a second component along with the gelation component CBTC to induce gel formation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Sureshan and co-workers have demonstrated the use of a carbohydrate-based gel system in oil spill remediation and ion sequestration, which is considered a major environmental concern. Soft material fabricated from 1,3:2,4-dibenzyldene-D-sorbitol (DBS) displayed stimuli-responsive behavior with respect to pH and UV irradiation in the presence of diphenyl iodonium nitrate forming photo-patterned multidomain gels . In addition, acetal-protected D-sorbitol displays robust self-assembly behavior, which is greatly influenced by the solvent used. In continuation of our ongoing research in the field of supramolecular chemistry, we have designed a gelator from D-sorbitol, an FDA-approved molecule bearing the E number 420 displaying applications in food, cosmetics, and pharmaceutical industries, and pyrene-1-carboxaldehyde.…”
Section: Introductionmentioning
confidence: 99%